1982
DOI: 10.1002/bjs.1800690111
|View full text |Cite
|
Sign up to set email alerts
|

Report of a prospective trial of dextranomer beads (Debrisan) and silicone foam elastomer (Silastic) dressings in surgical wounds

Abstract: A prospective randomized controller trial of dextranomer beads (Debrisan) and silicone foam elastomer (Silastic) dressings in open infected surgical wounds has been performed. The results indicate that the healing time for wounds treated by Debrisan (n = 25) and elastomer (n = 25) is similar, being 40.92 +/- 3.98 and 36.90 +/- 3.18 days respectively. The time taken for wounds to become pain-free was similar in both treatment groups, as was the persistence of signs in the wounds of erythema, oedema and slough. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Study sizes ranged from 20 to 80 patients and a total of 611 patients were included. Six trials recruited patients with pilonidal sinuses after incision or excision15–17, 21, 22, 25, five described patients with postoperative abdominal wound breakdown18–20, 23, 24, one studied patients with perineal wounds after excision of the rectum13, and one included patients with below‐knee amputation wounds25.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study sizes ranged from 20 to 80 patients and a total of 611 patients were included. Six trials recruited patients with pilonidal sinuses after incision or excision15–17, 21, 22, 25, five described patients with postoperative abdominal wound breakdown18–20, 23, 24, one studied patients with perineal wounds after excision of the rectum13, and one included patients with below‐knee amputation wounds25.…”
Section: Resultsmentioning
confidence: 99%
“…Pain was reported in six of the 13 RCTs13, 18, 20, 21, 22, 24, but it was measured in different ways, such as the need for analgesia, and on a four‐, ten‐ or 100‐point visual analogue scale (VAS). In all of the five trials comparing gauze with a modern dressing, patients dressed with gauze experienced significantly more pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 2,5 have been performed to evaluate the use of foam elastomer dressings and it is generally accepted that the method is simple to use and associated with substantially less pain both generally and at the time of dressing changes for the patient. Some studies have suggested that this method involves less nursing time, 1 enhances the rate of wound healing 2 and may facilitate an earlier return to work for the patient. For these reasons some authorities now recommend the routine use of foam elastomer in certain situations.…”
Section: Introductionmentioning
confidence: 99%